Utilization of Cellular Glass Insulation Waste in Construction Materials - Thitikorn Buasomboon; Orathai Chavalparit (Applied Environmental Research, 2014)
This research investigated the feasibility of using cellular glass insulation waste as fine aggregate in concrete paving block production. The effect of mixing proportions of cellular glass insulation waste at 0-40 % by volume was studied. Results show that the amount of cellular glass waste can be used as a substitute for fine aggregate or sand up to 20 %. Concrete specimens tested for compressive strength were found to be within an acceptable range of the interlocking concrete block paving standard set by Thailand Industrial Standards Institute. The compressive strength at 28 d was 41.50 MPa, with density ranging from 2.18 to 2.20 g cm-3. Thus, recycling of cellular glass wastes for concrete paving block production can reduce expenditures in purchasing natural aggregates and can minimize environmental impact attributed to solid waste disposal.